Relationship between right ventricular pacing and non-sustained ventricular arrhythmias in patients with dual-chamber pacemaker and normal range left ventricular ejection fraction - Rayan S. El-Zein; Anish K. Amin; Sreedhar R. Billakanty; Eugene Y. Fu; Allan J. Nichols; Steven D. Nelson; James M. Kleman; Gregory A. Kidwell; Nagesh Chopra (International Journal of Arrhythmia, 2020)
Abstract Background Right ventricular pacing (RVP) increases heart failure, AF, and death rates in pacemaker patients and ventricular arrhythmias (VAs) in defibrillator patients. However, the impact of RVP on VAs burden and its clinical significance in pacemaker patients with normal range LVEF of > 50–55% remains unknown. We sought to evaluate the relationship of RVP and VAs and its clinical impact in a pacemaker patient population. Methods Records of 105 patients who underwent de novo dual-chamber pacemaker implant or a generator change (Medtronic™ or Boston Scientific™) for AV block and sinus node disease at a tertiary care center between September 1, 2015, and September 1, 2016, were retrospectively reviewed. Results Data from 105 patients (51% females, mean age 76 ± 1 years, mean LVEF 61 ± 0.7%) without history of VAs (98.2%) were reviewed over 1044 ± 23 days. Dependent patients (100% RVP) exhibited the lowest VAs burden when compared to < 100% RVP (isolated PVCs, PVC runs of < 4 beats, and NSVT; p ≤ 0.001). Patients with < 1% RVP also exhibited low VA burden with intermediate RVP (1–99.9%) being most arrhythmogenic for PVC runs (p = 0.04) and for isolated PVCs (p = 0.006). Antiarrhythmics/beta and calcium channel blockers use and stress tests performed to evaluate VAs which were positive requiring intervention did not differ significantly. Burden of > 1/h of PVC runs and increasing PVC runs/h were significantly associated with hospitalization (p = 0.04) and all-cause mortality (p = 0.03), respectively. Conclusions In pacemaker patients with normal range LVEF (> 50–55%), 100% RVP is associated with the lowest burden of NSVT. Furthermore, patients with < 1% RVP also exhibit low VA burden; however, intermittent RVP seems to significantly correlate with non-sustained VAs.